2006
DOI: 10.1159/000095282
|View full text |Cite
|
Sign up to set email alerts
|

Round Window Stimulation with an Implantable Hearing Aid (Soundbridge®) Combined with Autogenous Reconstruction of the Auricle – A New Approach

Abstract: Background: Congenital malformations of the auricle are often combined with atresia of the outer ear canal and malformations of the ossicles, representing aesthetic as well as functional deficits. Optimal treatment should therefore address both aspects equally. This report describes a new approach, combining the reconstruction of the auricle with implantation of an active middle ear hearing aid, stimulating the round window membrane. Method: A 33-year-old male patient, with bilateral ear microtia, fibrous atre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
0
11

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 33 publications
1
65
0
11
Order By: Relevance
“…However, coupling the transducer to an ossicle is difficult in ears with middle ear disease, such as congenital aural atresia and ossicular malformation. An alternative way of coupling sound to the cochlea by driving the round window membrane (RWM), called reverse drive, was developed, and some preliminary studies on middle ear implantable devices have been reported (Colletti et al 2006(Colletti et al , 2009Kiefer et al 2006;Beltrame et al 2009;Linder et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…However, coupling the transducer to an ossicle is difficult in ears with middle ear disease, such as congenital aural atresia and ossicular malformation. An alternative way of coupling sound to the cochlea by driving the round window membrane (RWM), called reverse drive, was developed, and some preliminary studies on middle ear implantable devices have been reported (Colletti et al 2006(Colletti et al , 2009Kiefer et al 2006;Beltrame et al 2009;Linder et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Bei Kindern mit Gehörgangs-und Ohrmuschelatresien kann die kosmetische Rehabilitation mit einer Hörgeräteimplantation verbunden werden [4,7]. Eine wichtige Indikation stellt die Versorgung von Patienten mit chro- …”
Section: Einführung Zum Themaunclassified
“…[6][7][8] However, recent research has been focusing on the use of a round window. [9][10][11][12] There are 2 opening windows into the inner ear. The one is oval window and the other is round window.…”
Section: Introductionmentioning
confidence: 99%